Problematika Pendidikan TK Al-Qur’an dalam Menyiapkan Generasi Qur’ani di Kota Balikpapan - Basri , Basri (Program Pascasarjana Universitas Ibrahimy, 2018)
Progress of a nation is determined by quality of education of nation itself. There are several factors that affect the quality of education such as the subject of educators, materials and supporting facilities. One of the basic educational institutions that contribute to the quality of education this country is educational institutions in community starting from Kindergarten school. Kindergarten al-Qur'an and early childhood of the Qur'an. The educational institution of the Qur'an today is growing very rapidly but on the other hand has not been directly proportional to the quality produced. This study discusses of Qur'anic educational problems preparing the Qur'anic generation seen from the point of view of management and implementation education of the Qur'an in institution. The results of this study indicate that the educational institutions of al-Qur'an are still experience problems in the management such as the responsibility of managers, the managerial capability of the unit head, and the ability to provide supporting facilities, in the implementation of learning, there are many educational institutions that do not match the ratio of the number of teachers with one study group on the other hand, the quality of teachers are still low and the ability of teachers transfer knowledge to students.